Air Mobility, Ten Heads and Universal Authority: Constructing Ravana in the Folk Imagination of Sabaragamua - A Folkoric Study - Lal Medawattegedara (The Open University of Sri Lanka, 2021)
King Ravana has already attained a cult status in modern Sri Lanka owing to a resurgence of texts about the legendary king that suddenly flooded the bookshops as well as the mass media. Yet, unseen by this phenomenon, a folktale collection focusing on Ravana was released for public consumption by Gunasekera Gunasoma under the titled Sabaragamuwa Ravana Jana Katha (Ravana Folktales of the Sabaragamuwa Region). This study undertakes a re-reading of these folktales using the folkloric postulate of 'folk ideas' in order to locate the modes of construction of the personality of 'King Ravana' and the insights such constructions might offer into the material conditions of the story creators/tellers/listeners. Folktales tend to carry cultural assumptions, as well as cultural prejudices, of common folks through the implicitly embedded 'folk ideas' in their narratives and this study intends to locate such 'silent' articulations and analyse them to understand a group of people's own perceptions about the notions of leaders and leadership.